2015
DOI: 10.1016/j.jcps.2015.06.002
|View full text |Cite|
|
Sign up to set email alerts
|

“I” value justice, but “we” value relationships: Self‐construal effects on post‐transgression consumer forgiveness

Abstract: Causal attributions and brand‐relationships are known to determine how consumers react to brand transgressions. Considering both transgression controllability and brand‐relationship strength, the authors show that self‐construal moderates consumer reactions to brand transgressions. Three studies using different product and service failure scenarios demonstrate that consumers who have independent self‐construals are more forgiving when the brand has no control over the transgression, regardless of brand‐relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 42 publications
4
99
1
Order By: Relevance
“…Prior research has shown that source (i.e., company, person) errors tend to create negative inferences (Chesney & Su, ; Palmer et al, ) and, as a consequence, may generate retaliation (Grégoire & Fisher, , ). However, we focus on how a source error may have a positive consequence (Kupor et al, ; Sinha & Lu, ). In particular, the results suggest that if consumers expected an error and it eventually happened, then they may create positive inferences regarding source trustworthiness (Holmes & Rempel, ) because it was consistent with their expectations, which may also influence their loyalty toward the source (Aaker, ; Chaudhuri & Holbrook, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has shown that source (i.e., company, person) errors tend to create negative inferences (Chesney & Su, ; Palmer et al, ) and, as a consequence, may generate retaliation (Grégoire & Fisher, , ). However, we focus on how a source error may have a positive consequence (Kupor et al, ; Sinha & Lu, ). In particular, the results suggest that if consumers expected an error and it eventually happened, then they may create positive inferences regarding source trustworthiness (Holmes & Rempel, ) because it was consistent with their expectations, which may also influence their loyalty toward the source (Aaker, ; Chaudhuri & Holbrook, ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, this work advances our knowledge of how errors might influence consumer behavior. Although consumers typically form negative inferences about companies and individuals who make errors (Chesney & Su, ; Palmer, Simmons, & de Kervenoael, ), mistakes can also result in positive outcomes (Kupor, Reich, & Laurin, ; Sinha & Lu, ). In this study, we suggest that source trustworthiness after an incorrect estimate is dependent upon its level of imprecision.…”
mentioning
confidence: 99%
“…According to Roloff et al (2001) , committing transgressions – the violation of rules governing a relationship – allows people to learn about the qualities of others involved in the relationship and affords them the opportunity to investigate a wide range of unpredicted and inappropriate behaviors across diverse relationship types ( Metts, 1994 ). The consumer–brand relationship is no exception, but despite its importance, the empirical investigations of the consumer–brand relationship regarding transgressions are largely focused only on the service domain ( Smith et al, 1999 ; Hedrick et al, 2007 ) and consumers’ post-transgression reactions ( Sinha and Lu, 2016 ). Thus, understanding the influence of various types of transgressions (mis)aligned with brand positioning in the consumer–brand relationship, as well as the underlying mechanism explaining the influence ( Aaker et al, 2004 ), is limited.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Whereas interdependents tend to prefer identity‐linked products when that identity is under threat, independents tend to avoid the existing identity connection in order to maintain positive self‐worth (White, Argo, & Sengupta, 2012). Compared to independents, interdependents focus more on their brand relationships, and are more likely to forgive a transgressing brand (involved in product or service failures) with which they have strong connections (Sinha & Lu, 2016).…”
Section: Conceptual Backgroundmentioning
confidence: 99%